A synthetic mRNA cell reprogramming method using CYCLIN D1 promotes DNA repair, generating improved genetically stable human induced pluripotent stem cells. (3rd March 2021) - Alvarez‐Palomo, Ana Belén; Requena‐Osete, Jordi; Delgado‐Morales, Raul; Moreno‐Manzano, Victoria; Grau‐Bove, Carme; Tejera, Agueda M.; Otero, Manel Juan; Barrot, Carme; Santos‐Barriopedro, Irene; Vaquero, Alejandro; Mezquita‐Pla, Jovita; Moran, Sebastian; et al.
Abstract: A key challenge for clinical application of induced pluripotent stem cells (iPSC) to accurately model and treat human pathologies depends on developing a method to generate genetically stable cells to reduce long‐term risks of cell transplant therapy. Here, we hypothesized that CYCLIN D1 repairs DNA by highly efficient homologous recombination (HR) during reprogramming to iPSC that reduces genetic instability and threat of neoplastic growth. We adopted a synthetic mRNA transfection method using clinically compatible conditions with CYCLIN D1 plus base factors ( OCT3/4, SOX2, KLF4, LIN28) and compared with methods that use C‐MYC . We demonstrate that CYCLIN D1 made iPSC have (a) lower multitelomeric signal, (b) reduced double‐strand DNA breaks, (c) correct nuclear localization of RAD51 protein expression, and (d) reduced single‐nucleotide polymorphism (SNP) changes per chromosome, compared with the classical reprogramming method using C‐MYC . CYCLIN D1 iPSC have reduced teratoma Ki67 cell growth kinetics and derived neural stem cells successfully engraft in a hostile spinal cord injury (SCI) microenvironment with efficient survival, differentiation. We demonstrate that CYCLIN D1 promotes double‐stranded DNA damage repair predominantly through HR during cell reprogramming to efficiently produce iPSC. CYCLIN D1 reduces general cell stress associated with significantly lower SIRT1 gene expression and can rescue Sirt1 null mouse cell reprogramming. In conclusion, we show synthetic mRNA transfection of CYCLIN D1 repairs DNA during reprogramming resulting in significantly improved genetically stable footprint in human iPSC, enabling a new cell reprogramming method for more accurate and reliable generation of human iPSC for disease modeling and future clinical applications. Abstract : Proposed clinical grade method to make better genetically stable human iPSC for clinical applications. CYCLIN D1 generated human iPSC have significantly improved genomic stability than current clinical grade methods that use C‐MYC, and thus clinically advantageous to reduce risk for long term cell replacement transplant strategies or accurate disease modeling.